Penilaian Kualitas Layanan E-Government Dengan Pendekatan Dimensi E-Govqual dan Importance Performance Analysis (IPA) (Studi Kasus Pada Pemerintah Provinsi Nusa Tenggara Barat) - Rino Agus Saputra; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
West Nusa Tenggara Province has implementing e-Government by creating a website as a part of public service. Public gave a 40.2% rating for poor assessment to the current website service. Public services should be periodically evaluated for service optimization. The study aims to determine the quality of West Nusa Tenggara Province website services using the dimensions of e-Govqual and IPA, determine the priority attributes of service quality improvement based on the results of IPA analysis and give the recommendations from the e-Govqual dimension attribute analysis. The study was conducted on the West Nusa Tenggara Province website at www.ntbprov.go.id during March 2017 to June 2017. To assess the quality of the website service used 5 dimensions and 28 e-Govqual attributes. With the 100 respondents used as research samples, the results of IPA analysis on the level of conformity has an average value of 85.22% and value of the gap has a value of GAP 0 is -0.61, meaning the performance of the website service has not been able to meet user expectations. Furthermore, from the quadrant analysis, 4 attributes with main priority and 8 attributes with low priority for service improvement. Recommendations are given based on literature or theory for attributes that need to be improved in order to improve the quality of website services.